Conflict Dynamics and Prospects for Peacebuilding in Iraq: A Case Study of Post Saddam Era - Intizar, Mahnoor; Arshad, Farooq; Shafiq, Sobia Nasir; Abbas, Zainab (Pakistan Journal of Humanities and Social Sciences, 2025)
This study seeks to understand the multidimensional dynamics of post-2003 Iraq and the conflict that engulfed it after the American intervention. It describes the violent struggles for power that ensued after Baathist rule in Iraq formulated due to sectarian divides, governance issues, alien involvement, and the emergence of violent radical factions. At the same time, this research seeks to analyze the nature and consequences of historically rooted grievances, the process of de-Ba'athification, and power voids that led to long-term persistent violence that balkanized the Iraqi society along sectarian lines and gave rise to extremist entities such as ISIS. These actors pose serious challenges not only to the affected state but to the entire regional and global security order. Furthermore, the research sheds light on peacebuilding interventions by both the local and international authorities including efforts at structural government system changes, reconciliation processes, and macroeconomic revitalization of the country. By utilizing a case study strategy, this work examines the success of chosen strategies at resolving violent conflict, identifying reasons why durable peace is not attainable. Evidence gathered from the study demonstrates that enduring peace in Iraq requires a profound resolution to the challenge of divided society which in contrast is absent in contemporary state-building policies. Vicky Culberston argues the thesis that a centralized, all-encompassing solution that integrates social, economic, and political change is the answer to enduring stability in Iraq.